Contaminação do lençol freático por hidrocarbonetos na região de Avaré - SP - Fogaça, Paulo Henrique de Campos [UNESP] (2015)
The contamination of water and soil is frequently caused by leakage and fuel can be prevented. Many incidents that contaminate the environmnent have occurred due to oil exploration and refining, as well as transport and storage of derivatives. As a result, the water table is reached by hazardous substances because they in most cases, carcinogenic, and depressants of the central nervous system. With CONAMA Resolution 273, from 2000, the water and soil of the regions where they are located fueling stations are now analyzed. Proven contamination, these sites have undergone a physical restructuring to adapt the storage tanks and service structure. In addition, the stations have the obligation to implement and effective remediation system, capable of making, again, water and soil appropriate to the services and the hman being without danger to health. This paper presents a study of soil contamination and remediation process and groundwater Avare region (SP) caused by gas stations and fuel supply in the region. Two different structures storage facilities were studied: buried tanks (Rank 1) and air tanks (Rank 2), and the data shown are from the reports prepared by CETESB on detailed investigation and remediation of these posts. Several analyzed of the soil and water were carried out by specialized companies, as well as monitoring and remediation of these. The main results show, for example, in relation to the first station, the quality of the local aquifer water found to be inadequate for eventual ingestion at thigh levels of concentration of benzene and toluene. After the remediation process, noted a reduction of concentrations of the chemical compounds of interest. The table near the station 2 also showed contamination due to diesel oil leaks. In this case, after the last period of analysis of the remediation process, there was a 100% effectiveness in remediation process